Secure and efficient application of MANET using Identity Based cryptography combined with Visual cryptography technique (International Journal of Engineering and Computer Science, 2014)
Data security is an important issue in military devices. This paper presents a secured and efficient way of sending data and image in encrypted form using Identity Based Cryptography and Visual Cryptography. This has direct application in MANETs specifically for military surveillance [16]. This paper also presents an advantage of using public - private key pairs in Visual Cryptography wherein generally only the private key generators are used. In this paper, the simplicity of RSA algorithm is adopted to set up the public - private key pairs of all the mobile nodes and hence for encryption and decryption [22]. Regeneration of public-private keys is adopted to make the system more secure from various attacks [6].